Two-dimensional phos-tag zymograms for tracing phosphoproteins by activity in-gel staining - Meisrimler, Claudia-Nicole; Schwendke, Alexandra; Lüthje, Sabine (Frontiers in Plant Science, 2015)
Protein phosphorylation is one of the most common post translational modifications regulating many cellular processes. The phos-tag technology was combined with two-dimensional zymograms, which consisted of non-reducing IEF PAGE or NEPHGE in the first dimension and high resolution clear native electrophoresis (hrCNE) in the second dimension. The combination of these electrophoresis methods was mild enough to accomplish in-gel activity staining for Fe(III)-reductases by NADH/Fe(III)-citrate/ferrozine, 3,3’-Diaminobenzidine/H2O2 or TMB/H2O2 in the second dimension. The phos-tag zymograms can be used to investigate phosphorylation-dependent changes in enzyme activity. Phos-tag zymograms can be combined with further downstream analysis like mass spectrometry. Non-reducing IEF will resolve proteins with a pI of three to ten, whereas non-reducing NEPHGE finds application for alkaline proteins with a pI higher than eight. Advantages and disadvantages of these new methods will be discussed in detail.